Implementasi Teknik Komunikasi Persuasif Pada Mata Pelajaran Aqidah Akhlak Kelas X di MA Darussalam Kalibaru Banyuwangi (Ar-Raudhah: Journal of Islamic Religious Education, 2025)
This study described the application of persuasive communication technique to Belief and Morals material. The persuasive communication technique in Belief and Morals material is communication that is psychologically oriented towards students in order to increase awareness to study religion for their future. Given the reality of students at this time very minimal in practicing the teachings of Islam. Even some students' morals are still not in accordance with Islamic teachings. Based on this background, the purpose of this study is to describe the implementation of persuasive communication technique in the Subject of Belief and Morals Class X at MA Darussalam Kalibaru in the 2024/2025 Academic Year To find out the inhibiting factors and factors supporting the implementation of persuasive communication methods in class X Belief and Morals subjects at MA Darussalam Kalibaru Banyuwangi Academic Year 2024/2025. To find out solutions to the inhibiting factors in implementing persuasive communication technique in class X Belief and Morals subjects at MA Darussalam Kalibaru Banyuwangi for the 2024/2025 Academic Year. The method used in this research is to use descriptive qualitative, with data collection techniques using observation, interviews, and documentation. the primary data sources are teachers of the Belief and Morals Class X MA Darussalam Kalibaru, class X students, and the school principal. research results from the implementation of persuasive communication methods in the of Belief and Morals subject in class X showed that persuasive communication methods are fairly effective learning methods, this was explained directly by the Belief and Morals teacher at the junior high school. Supported by teacher factors, student factors, facility factors and environmental factors that are sufficient to support the implementation of persuasive communication Technique. Even though there are inhibiting factors, Belief and Morals teachers can overcome them by being more creative and innovative in the learning process.